Stemi mimicking post COVID: a case of focal myopericarditis post COVID infection - Muhammad Atif Masood Noori; Abanoub Rushdy; Hardik Fichadiya; Sherif Roman; Islam Younes; Peter D. Lenchur; Peter M. Lenchur; Fayaz Shamoon (Greater Baltimore Medical Center, 2021)
Since the beginning of the coronavirus disease 2019 (COVID19) pandemic, several cases of myocarditis related to COVID-19 infection have been reported. These cases range from asymptomatic disease to fulminant heart failure or sudden cardiac death. Cardiac injury has also been found in asymptomatic patients and patients who recovered from the disease. Data regarding cardiovascular involvement due to COVID-19 infection are still limited, and the actual prevalence of myocarditis due to COVID-19 infection is still unknown. We present a case of focal myopericarditis in a patient recently recovered from COVID-19 pneumonia with electrocardiogram showing ST elevation in inferior and lateral leads. This case highlights the need for studying the long-term cardiovascular complications of COVID-19 and reinforces the use of cardiac magnetic resonance (CMR) and cardiac biomarkers in the diagnosis of COVID-19-related myocarditis.